Long-term outcomes of radiofrequency ablation and cyanoacrylate closure for treatment of small saphenous veins - Ahmet Kayan; Ali Fuat Karacuha; Nur Dikmen; Cagdas Baran; Mustafa Sirlak (Turkish Journal of Vascular Surgery)
Aim: Superficial venous insufficiency is less prevalent in the lesser saphenous vein compared to the great saphenous vein. Treating the lesser saphenous vein often presents greater challenges due to its proximity to the sural nerve and anatomical variations. This study evaluates the long-term efficacy of radiofrequency ablation (RFA) and cyanoacrylate closure (CAC) for managing small saphenous veins and discusses our treatment approach. Material and Methods: We performed a retrospective analysis involving 137 patients (64 treated with CAC and 73 with RFA) who received treatment for small saphenous vein insufficiency at our clinic between 2014 and 2019. We assessed quality of life and clinical outcomes at 6 months, and at 1, 3, and 5 years post-treatment. Results: Our findings indicated that radiofrequency ablation showed greater improvements compared to cyanoacrylate embolization in terms of VCSS. However, over the 5-year follow-up period, recurrence rates were observed in 11 (17.1%) patients in the CAC group and 5 (6.8%) patients in the RFA group, with this difference being statistically significant (p=0.045). Conclusion: Radiofrequency ablation for treating venous insufficiency offers superior long-term quality of life benefits compared to cyanoacrylate closure, particularly after three years. [Turk J Vasc Surg 2024; 33(3.000): 139-45]